An online testing design choice typology towards cheating threat minimisation - Munoz, Albert; Mackay, Jonathon (Journal of University Teaching and Learning Practice, 2019)
Online testing is a popular practice for tertiary educators, largely owing to efficiency in automation, scalability, and capability to add depth and breadth to subject offerings. As with all assessments, designs need to consider whether student cheating may be inadvertently made easier and more difficult to detect. Cheating can jeopardise the validity of inference drawn from the measurements produced by online tests, leading to inaccurate signals and misperceptions about what students know and can do. This paper extends theoretical understanding about cheating behaviours to link online test design choices and their influence on a student’s capability and willingness to cheat. This research reviews the literature on cheating theories and a typology construction methodology to relate common online test design choices to their cheating threat consequence. In doing so, the typology offers educators designing online tests general normative guidance aimed at reducing threats to assessment inference validity, and academic integrity in general, brought about by student cheating. While we admit that cheating cannot be completely eliminated in online testing, the guidance provided by the typology can assist educators to structure online tests to minimise cheating.